Penerapan sistem keamanan koleksi pada Perpustakaan Kota Yogyakarta - Gustina Erlianti (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2017)
Yogyakarta City Library as the pride of information literacy should be able to provide optimal services to the librarian. One way that can be done is to provide a complete and latest collection so that their information needs are met. But in the fulfillment of information needs, not infrequently pemustaka who perform acts of vandalism (destruction of the collection) even recorded some missing books and did not return to the library. Things to note related to the problem is the application of security systems implemented by a library. Therefore this paper aims to find out how the application of security system collection in Yogyakarta City Library. The method used by the author in this article is qualitative descriptive that is by conducting interviews and observations to the Yogyakarta City Library. From the results obtained, the overall security system used by the Yogyakarta City Library is quite good, ranging from the physical aspects (doors and windows) that already use the trellis so as not easily accessed by thieves, the use of CCTV to monitor all activities in the library, tighten lending With collateral to minimize damaged / lost books, locker provision and intense supervision of librarians and security personnel.